Microstrip and printed antenna design - Bancroft, Randy (SciTech Pub., 2009)
Gives a complete introduction to useful elegant microstrip antenna designs that may be engineered unlike many other designs. Provides extensive section on the design of omni-directional microstrip antennas. De-mystifies basic PIFA designs and expands on their limitations.